2017
DOI: 10.1167/iovs.16-20903
|View full text |Cite
|
Sign up to set email alerts
|

The Eye Drop Preservative Benzalkonium Chloride Potently Induces Mitochondrial Dysfunction and Preferentially Affects LHON Mutant Cells

Abstract: PurposeBenzalkonium chloride (BAK) is the most commonly used eye drop preservative. Benzalkonium chloride has been associated with toxic effects such as “dry eye” and trabecular meshwork degeneration, but the underlying biochemical mechanism of ocular toxicity by BAK is unclear. In this study, we propose a mechanistic basis for BAK's adverse effects.MethodMitochondrial O2 consumption rates of human corneal epithelial primary cells (HCEP), osteosarcoma cybrid cells carrying healthy (control) or Leber hereditary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 34 publications
4
57
0
4
Order By: Relevance
“…Here, we showed that BAC, even at low concentrations, induced dysfunction of mitochondria, inhibiting respiration in state 3, decreasing the membrane potential, promoting opening of the mPTP, potentiating hydrogen peroxide production by mitochondria, and severely blocking synthesis of ATP. Previously, it was reported that BAC inhibited mitochondrial ATP production and oxygen consumption in human corneal epithelial cells and cells bearing LHON mutations possibly by directly targeting mitochondrial complex I [48]. However, closer examination of this paper showed that the authors used permeabilized cells as models and, more importantly, inadequate, from the point of view of bioenergetics, "mitochondrial buffer" causing high-amplitude swelling of mitochondria with all the consequences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Here, we showed that BAC, even at low concentrations, induced dysfunction of mitochondria, inhibiting respiration in state 3, decreasing the membrane potential, promoting opening of the mPTP, potentiating hydrogen peroxide production by mitochondria, and severely blocking synthesis of ATP. Previously, it was reported that BAC inhibited mitochondrial ATP production and oxygen consumption in human corneal epithelial cells and cells bearing LHON mutations possibly by directly targeting mitochondrial complex I [48]. However, closer examination of this paper showed that the authors used permeabilized cells as models and, more importantly, inadequate, from the point of view of bioenergetics, "mitochondrial buffer" causing high-amplitude swelling of mitochondria with all the consequences.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, mitochondrial oxidative stress can influence pathogenesis and progression of age-related corneal diseases, as well as generalized corneal aging [47]. BAC at pharmacologically relevant concentrations inhibited mitochondrial ATP production and oxygen consumption in human corneal epithelial cells and cells bearing LHON mutations and osteosarcoma cybrid cells, possibly by directly targeting mitochondrial complex I [48,49]. The authors concluded that the findings obtained support the urgent need for additional research on the mitochondriarelated inhibitory effects of BAC [49].…”
Section: Introductionmentioning
confidence: 81%
“…[66]. In addition, BAC is the most active ingredient and widely used as a preservative in ophthalmic solutions [67]. Nevertheless, the usage of BAC has been linked to inducing considerable adverse consequences in humans.…”
Section: Benzalkonium Chloride and Its Cytotoxic Effectsmentioning
confidence: 99%
“…Strategies for enhanced delivery include drug reformulation into nanocapsules or nanospheres, reducing the amount of preservatives (which may illicit side effects [180]), or modulation of solution viscosity by incorporation of polymers, collagen shields, gels, or liposomes. Such engineering allows greater cell specificity and retention of stability.…”
Section: New Classes Of Drugmentioning
confidence: 99%